2019
DOI: 10.1364/ol.44.001809
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of weak deep ultraviolet pulses using cross-phase modulation scans

Abstract: Temporal pulse characterization methods can often not be applied to UV pulses due to the lack of suitable nonlinear crystals and very low pulse energies. Here, a method is introduced for the characterization of two unknown and independent laser pulses. The applicability is broad, but the method is especially useful for pulses in the deep UV, because pulse energies on the picojoule-scale suffice. The basis is a spectral analysis of the two interfering UV pulses, while one of the pulses is phase shifted by an un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…2 b). As previous studies [22,23] revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [22][23][24].…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…2 b). As previous studies [22,23] revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [22][23][24].…”
mentioning
confidence: 66%
“…As previous studies [22,23] revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [22][23][24]. V is beneficial for the interpretation of the data, because it is generated within the first few micrometers and maintains its spectrum in the subsequent linear propagation.…”
mentioning
confidence: 66%
“…For a further validation of the simulation results, the DUV waveforms are characterized with the recently developed method cross-phase modulation scans. 18 Spectra |E UV | 2 are recorded, while a further Vis-IR pulse, labeled R, is overlapped at a variable delay τ R , see Figure 1. The pulse characterization is performed both experimentally and on synthetic data, which is generated using the UPPE simulation, where all three pulses A, B, and R are initialized.…”
mentioning
confidence: 99%
“…In order to scrutinize the mechanism of harmonic concatenation, simulations are employed similar as described in refs and . The unidirectional pulse propagation equation (UPPE) is integrated numerically using the split-step method.…”
mentioning
confidence: 99%
See 1 more Smart Citation